Academic Perspectives on E-Learning in Higher Education Contexts - Briceño Nuñez, Chess Emmanuel (2024)
Virtual teaching in higher education, driven by technology and globalization, has garnered academic interest. This article explores epistemological, ontological, and axiological perspectives to understand virtual teaching. The importance of instructor self-assessment and student evaluation is emphasized. Background studies reveal research on virtual tutoring, educational technology, and teacher competencies. The theoretical framework addresses Constructivism, Activity Theory, and the Technology Acceptance Model. The quantitative methodology examines the perception of 30 teachers and 100 students. The results show consensus on clarity of material, effectiveness of multimedia resources, and attention to interaction. Additionally, shared concern for technological accessibility is highlighted. It is concluded that clear curriculum design and effective interaction are crucial for virtual teaching in higher education.